Tandem superelectrophilic activation for the regioselective chlorofluorination of recalcitrant allylic amines. Issue 5 (4th February 2016) - Le Darz, Alexandre; Castelli, Ugo; Mokhtari, Naima; Martin-Mingot, Agnès; Marrot, Jérôme; Bouazza, Fodil; Karam, Omar; Thibaudeau, Sébastien
Abstract: An efficient and straightforward regio-controlled route to β-fluoro-γ-chlorinated amines was developed via an ammonium–chloronium superelectrophilic activation in superacid HF/SbF5 . Through halogen directing effect the method was extended to a variety of (poly)halofluorinated building blocks amenable for further synthetic modifications. The direct synthesis of chlorofluorinated analogues of bioactive compounds via this process confirmed the ability to use this strategy for further applications in medicinal chemistry. Graphical abstract: